Rancang Bangun Aplikasi Transliterasi Aksara Bali Menjadi Huruf Latin Menggunakan Metode Rule Based Pada UTF-16 Berbasis Android - Aranta, Arik; Andika, I Gede (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2023)
Balinese script is a script that has been used by Balinese tribes since ancient times, as evidenced by thediscovery of 2,103 ancient lontars using Balinese script in Klungkung, Bali. Currently, Google alreadyhas a virtual keyboard that can be downloaded to a smartphone. This Google keyboard already hasBalinese script mode that the letters was based on Unicode, but it still doesn't have a feature that canread Balinese script into Latin letters. By combining these two problems, a study was designed aboutmaking applications that can preserve Balinese script by utilizing the Balinese script keyboard featureprovided by Google to be transliterated into Latin letters. In this study, a rule based method is used toperform transliteration in order to be able to adjust to the rules of reading Balinese script correctly. It isalso used to provide ID for each Balinese character using hexadecimal based on the UnicodeTransformation Format-16 code for each character. The application was built by implementing of total940 rules and 33.253 words, after testing the application the result obtained from the transliterasionreach 99.4% of succeed from 1104 Balinese script words.